THE EFFECT OF ADDING AVOCADO-OIL ON THE NUTRITIONAL, MICROBIOLOGICAL AND RHEOLOGICAL PROPERTIES OF YOGURT - A. R. Mulakhudair; Z. R. Shati; D. I. Al-Bedrani; D. H. Khadm (مجلة الأنبار للعلوم الزراعية, 2024)
The avocado is a nutrient-rich fruit that has been shown to benefit health and diet qualities. In this study, avocado oil was added to milk for making yogurt to examine its effect on the chemical, rheological, microbial and sensory properties of yogurt. Avocado oil at 0.5%, 1% and 3 % and 5 % were added to the skim of reconstituted dried bovine milk. The developed yogurt was tested to evaluate the final product, including pH, chemical composition, acidity, and microbial properties as well as viscosity, spontaneous whey separation, water holding capacity, and hardness immediately following production and while being stored. Results show that yogurt made by adding 0.05% avocado oil had premium properties compared to the control and other additional treatments. More importantly, adding avocado oil enhanced its acceptability as well as provided more nutritious and healthy characteristics compared to plain yogurt. This is because avocado oil contains compounds of nutritional value, such as unsaturated fatty acids (MUFA and PUFA), as well as having compounds with biological activity, such as tocopherols, tocotrienols, phytosterols, carotenoids, and polyphenols, that help protect against diseases through the diet